Aplikasi Sebaran Tempat Kursus dan Bimbingan Belajar Wilayah Bandar Lampung Berbasis Android - Didik Kurniawan; Gita Ferdina Anggraini (Jurnal Komputasi, 2017)
Course and tutoring is a non-formal institution that serves students' education outside of school hours. Currently, courses and tutoring have become a necessity for students to college students, ranging from kindergarten (kindergarten), elementary school (SD), junior high school (SMP), high school (SMA) to college. In Bandar Lampung City there are many courses and tutoring scattered in every district in Bandar Lampung City. But with many courses and tutoring, people still difficult to find information about the place of the course and tutoring. For that, need to be built application distribution of course and tutoring in Bandar Lampung based on Android. This application is built using Waterfall method. In this application  user can see the map of distribution of  course and tutoring area of Bandar Lampung, see information about each place of course and tutoring, that is covering address information, contact and cost, user also can search for the nearest course and tutoring. This  application was tested using black-box method. The results of research data using a questionnaire can be concluded that the application gets a percentage value of 88.4% belonging to the category very well according to the respondents were selected randomly.